Material recycling of high hardness solid polyurethanes - Ryszkowska, J.; Markiewic, B. (Polimery, 2022)
High hardness cast polyurethanes (PURM) filled with waste polyesterurethanc powder hardness similar to new PURMs were investigated. A process for manufacturing such recycled products without micropore defects was developed. Effect of recycled material content (up 20% by weight) and grain size of waste (non-fractionated with grain size under 1.5 mm and fractionated 0.4 - 1.0 mm, see Table 1) on mechanical properties (Young's modulus, tearing strength, tensile strength, abrasive wear, elongation at break, and number of cycles to break - see Figs. 3-14) was determined. Results show that recycled PURMs may be treated as powder compositions. Low disintegration and logistics costs of the investigated waste llow reduction of PURM manufacturing costs by 14-19%.